The Use of Technology in the ‘Third Age’: Findings from the Effects of Digital Technology on Seniors (EDITS) Project - Quan-Haase, Anabel; Martin, Kim; Schreurs, Kathleen (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2016)
Twenty-one seniors (aged 60+) were interviewed about their use of digital technology. Grounded theory and Key Point analysis were used to identify several areas where these tools have become embedded into the lives of seniors. These include information seeking, news media, library usage, and reading preferences. Vingt et un aînés (âgés de 60 ans et plus) ont été interrogés sur leur utilisation des technologies numériques. Nous avons utilisé la théorie ancrée dans les données empiriques et l’analyse de point clé pour identifier plusieurs domaines dans lesquels ces outils se sont intégrés dans la vie des aînés. Ceux-ci comprennent la recherche d’information, les nouvelles, l’utilisation de la bibliothèque et les préférences de lecture.